Intercultural communication an advanced resource book for students - Holliday, Adrian; Kullman, John, 1957-; Hyde, Martin, 1960- (Routledge applied linguistics, 2021)
"Intercultural Communication provides a critical introduction to the dynamic arenas of communication across different cultural and social strata. Throughout this book, topics are revisited, extended, interwoven and deconstructed, with the reader's understanding strengthened by tasks and follow-up questions. The updated fourth edition of this popular textbook has been updated to feature: new readings by Kwame Antony Appiah, Yoshitaka Miike, Edward Ademolu and Siobhan Warrington, Helena Liu, Michael Zirulnik and Mark Orbe, which reflect the most recent developments in the field; refreshed and expanded examples and tasks including new material on an Asia-centric approach to intercultural communication, selfies as a global discourse, the impact on intercultural communication of English as a lingua franca in multinational organisations, and representations of Africa in charity media campaigns; extended discussions of topics including intercultural training, voluntourism, challenging essentialism in business contexts and intersectional approaches to identity; revised further reading suggestions. Written by experienced teachers and researchers in the field, Intercultural Communication, Fourth edition provides an essential textbook for advanced students studying this topic"--